Comparison of examples of child sexual abuse cases in Turkish and British media: protection of children's rights - Akpınar, Ayşe (My University, 2019)
This study compares news articles which have documented child sex abuse cases in Turkish and UK press in terms of their lexical choices and the level of details which they conceal in order to protect the rights of the child. The aim is to shed light on the significance afforded to the protection of children in both countries. Furthermore, the causes and consequences of child sex abuse will be discussed with mention of the various laws and penalties enforced to deter such acts
Keywords: Child sexual abuse, children’s rights, Turkish Press, British Press